Design of ring antenna for next-generation wireless application - Goh, Wilson Ting Huang (Nanyang Technological University, 2024)
This final year report focuses on designing and optimizing a ring antenna for use in nextgeneration wireless applications across the Ku, K and Ka Bands. By means of an organized methodology that includes a review of the literature, simulation studies and experimentation, the project seeks to attain optimal performance characteristics that are customized to meet the needs of modern wireless communication systems. A number of design variations are investigated, mostly concentrating on varying the distance between rings in order to modify coupling levels and optimize frequency response. Four different frequency bands are included in the final design. Despite challenges such as time constraints and the inability to fabricate prototypes for physical testing, the project provides valuable information about antenna performance improvement, coupling management, and potential future research development directions.